Mechanisms of gas transfer impairment utilizing nitric oxide following severe COVID‐19 pneumonitis. Issue 7 (5th April 2023) - Seccombe, Leigh M.; Heath, David; Farah, Claude S.; Di Michiel, James R.; Veitch, Elizabeth M.; Peters, Matthew J.
Abstract: Reduced carbon monoxide diffusing capacity (DLCO ) is common after recovery from severe COVID‐19 pneumonitis. The extent to which this relates to alveolar membrane dysfunction as opposed to vascular injury is uncertain. Simultaneous measurement of nitric oxide diffusing capacity (DLNO ) and DLCO can partition gas diffusion into its two components: alveolar–capillary membrane conductance (DmCO ) and capillary blood volume (VC ). We sought to evaluate DmCO and VC in the early and later recovery periods after severe COVID‐19. Patients attended for post‐COVID‐19 clinical review and lung function testing including DLNO /DLCO . Repeat testing occurred when indicated and comparisons made using t ‐tests. Forty‐nine (eight female) subjects (mean ± SD age: 58 ± 13, BMI: 34 ± 8) who had severe COVID‐19 pneumonitis, WHO severity classification of 6 ± 1, and prolonged (21 ± 22 days) hospital stay, were assessed 2 months (61 ± 35 days) post discharge. DLCO adj ( z ‐score −1.70 ± 1.49, 25/49 < lower limit of normal [LLN]) and total lung capacity ( z ‐score −1.71 ± 1.30) were both reduced. DmCO and VC and were reduced to a similar extent ( z ‐score −1.19 ± 1.05 and −1.41 ± 1.20, p  = 0.4). Seventeen (one female) patients returned for repeat testing 4 months (122 ± 61 days) post discharge. In this subgroup with more impaired lung function, DLCO adj improved but remained below LLN ( z ‐score −3.15 ± 0.83 vs. −2.39 ± 0.86, p  = 0.01), 5/17 improved to >LNN. DmCO improved ( z ‐score −2.05 ± 0.89 vs. −1.41 ± 0.78, p  = 0.01) but VC was unchanged ( z ‐score −2.51 ± 0.55 vs. −2.29 ± 0.59, p  = 0.16). Alveolar membrane conductance is abnormal in the earlier recovery phase following severe COVID‐19 but significantly improves. In contrast, reduced VC persists. These data raise the possibility that persisting effects of acute vascular injury may contribute to gas diffusion impairment long after severe COVID‐19 pneumonitis. Abstract : Simultaneous measurement of nitric oxide and carbon monoxide diffusing capacity (DLNO /DLCO ) was used to quantify the contributions of alveolar–capillary membrane conductance and capillary blood volume (VC ) to impaired gas diffusion following severe COVID‐19. At 2 months, both were reduced to a similar extent. Membrane conductance significantly improved at 4 months, however, VC remained reduced. These novel findings suggest persisting vascular injury may contribute to physiological impairment long after severe COVID‐19 pneumonitis.